Lexical Variation of Agam Tanah Datar Dialect in Nagari Gunuang of Padang Panjang City - Hijrianda Niko Larizky; Chattri Sigit Widyastuti (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This study discusses linguistic phenomena regarding the lexical variations of the Agam Tanah Datar dialect found in Nagari Gunuang, Padang Panjang City. The research conducted in Nagari Gunuang covered four villages as observation points, namely Ekor Lubuk village, Sigando village, Ganting village and Ngalau village. This study describes the forms of lexical variations of the Agam Tanah Datar dialect of the Minangkabau language found in Nagari Gunuang, Padang Panjang City. The data of this study are the dialects spoken orally by nine informants. The informants of this study were the natives of Nagari Gunuang who directly explained 851 glosses of vocabulary, phrases and sentences. This research is a qualitative as well as quantitative research. The method of providing data used is the method of observing, noting, and speaking. The method of data analysis uses dialectometric calculations, in order to determine the percentage of speech differences between observation points. In this study, 172 lexical variations were found from 851 glosses which were grouped into: two two-symbol etimonsss, two three-symbol etimonss, two four-symbol etimonsss and three three-symbol etimonss. In the dialectometric calculation, it was found that the overall average percentage was below 25% which was classified as a speech difference.